O patrimônio cultural e os livros didáticos de História ou de como se constrói o sentimento de pertencimento (Brasil - 2000-2015) - Oliveira, Almir Félix Batista de (2016)
This doctorate study aims to examine (investigate, characterize and understand) the relationships entertained in Brazil between most recent historiography (academic and academic history) and didactic historiography, in other words, the writing for elementary's school students and teachers consumption (History textbook), with regard to the concept cultural heritage. From the analysis of four collections of the first phase of Basic Education that were approved in the assessments made by the National Textbook Program (PNLD) 2004, 2007, 2010 and 2013, we sought to understand how this concept appears in those textbooks. We seek to identify the ways that the didactic historiography appropriates the thesis about cultural heritage developed in recent years and produced, sometimes by historians with the changes in historical science, or by other professionals (architects, anthropologists, geographers, etc.) that have addressed this theme. For further, we also seek to understand how the teaching of history (identity trainer) using textbooks of history (didactic historiography) and with the measurement history teacher can ensure learning that takes into account the recognition the other and of cultural diversity